2012
DOI: 10.1136/neurintsurg-2012-010435
|View full text |Cite
|
Sign up to set email alerts
|

A thromboembolic model for the efficacy and safety evaluation of combined mechanical and pharmacologic revascularization strategies

Abstract: Background and purposeRecanalization strategies mediated by intra-arterial fibrinolytic therapy in combination with mechanical clot disruption may be a more effective treatment approach than either therapy used alone. There are few preclinical animal models to evaluate these strategies. Here we report on a model to simultaneously evaluate both of these treatment approaches.MethodsAllogeneic clot was injected through the 6 F guide catheter after creating >50% luminal stenosis of the common carotid arteries of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In our model, because of the extensive network of collaterals within the circle of Willis and MCA branches, we measured reperfusion with the TICI score rather than recording changes in pressure and flow gradients. Although recanalization scales can be applied to thrombectomy experiments conducted in animal models, high costs associated with such experiments and differences in anatomy are potential limiting factors 15 16…”
Section: Discussionmentioning
confidence: 99%
“…In our model, because of the extensive network of collaterals within the circle of Willis and MCA branches, we measured reperfusion with the TICI score rather than recording changes in pressure and flow gradients. Although recanalization scales can be applied to thrombectomy experiments conducted in animal models, high costs associated with such experiments and differences in anatomy are potential limiting factors 15 16…”
Section: Discussionmentioning
confidence: 99%
“…4 We found that vasospasm occurred in 100% of the swine subjects, to at least some extent on all stent retriever passes. Vasodilators (both verapamil and nitroglycerin) ultimately helped to resolve this.…”
Section: Procedure-related Vasospasmmentioning
confidence: 99%
“…Others have popularized rabbit models, which more closely mirror human responses to thrombolytics, but involve smaller rabbit blood vessels. 4,7 The swine model, as used by many others, allows for easy translation of skills from the model to patients, based on similar size and vasculature. After insertion of the femoral sheath via cutdown, the procedure was otherwise a high-fidelity replication of the procedural environment in stroke intervention.…”
Section: Discussionmentioning
confidence: 99%
“…21 Briefly, autologous, whole arterial blood was combined with bovine thrombin (2.5 U/mL blood) and coagulated in a 10 mm silicone tube and then allowed to age for 3 hours in normal saline at room temperature; clots with a 2.7 mm diameter were used for the creation of vascular occlusion. A cut down to the femoral artery was performed for placement of a 6F hemostatic introducer using a modified Seldinger technique.…”
Section: Methodsmentioning
confidence: 99%
“…In this animal study, we used a previously published rabbit vascular occlusion model developed to study new endovascular devices coupled with thrombolysis. 21 We assessed the combination of the TEB technique with SA-NT-targeted IA r-tPA delivery in this large vessel occlusion model. Our intention was to compare this novel technique to various control groups with particular attention to its efficacy and safety.…”
Section: December 2015mentioning
confidence: 99%